Spontaneous rupture of a left omental artery aneurysm treated by transcatheter arterial embolization: A case report. (October 2022) - Maghrebi, Houcine; Zaiem, Asma; Beji, Hazem; Jeribi, Bedis; Hadded, Anis; boukriba, Seif; Frikha, Wassim; Hamissa, Selim; Jouini, Mohamed; Kacem, Montasser
Abstract: Background: Omental artery aneurysms are extremely rare. Their rupture is related to high mortality and often treated by open surgery. We describe a case of a spontaneous rupture of a left omental artery aneurysm (OAA) that was successfully treated by transcatheter arterial embolization (TAE). Case presentation: A 68-year-old man presented with acute abdominal pain. On examination, he was hypotensive and tachycardic with a blood pressure of 90/50 mm Hg. He had diffuse abdominal distension and tenderness. An abdominal enhanced computed tomography scan (CT) showed a rupture of the left OAA responsible for moderate hemoperitoneum. We performed a successful TAE. Conclusion: Ruptured OAA causes high mortality. OAA represents the rarest form of splanchnic artery aneurysms. Interventional radiology permits to avoid unnecessary surgery. TAE is a safe procedure to control ruptured OAA. We highlight the importance of a rapid embolization if the patient is hemodynamically stable. Highlights: Omental artery aneurysms (OAA) are extremely rare. Ruptured OAA causes high mortality. Transcatheter arterial embolization is a safe procedure to control ruptured OAA. In case of failure, surgical treatment should be performed timely.